Rethinking the dialogue between the verbal and the visual: methodological approaches to the relationship between religious art and literature (1400-1700) - Falque, Ingrid; Guiderdoni, Agnès (Brill's studies on art, art history, and intellectual history, 2023)
"Intermediality, figurability, iconotext, visual exegesis... There is no shortage of new ways to approach the relationship between text and image. The exploration of these relationships has been greatly renewed in recent decades, benefiting from the contributions of anthropology, psychoanalysis and semiotics, alongside more traditional fields such as literature, art history and cultural history. Focusing on the religious field between 1400 and 1700, the essays gathered in this volume intend to contribute to the exploration of these relationships by placing a significant emphasis on the methodological dimension of their case studies. The editors have deliberately adopted the broadest possible position by considering the relations between the visual and the verbal, in order to emphasize the phenomenological point of view from which the objects studied are examined. Contributors include Ralph Dekoninck, Anna Dlabačová, Grégory Ems, Ingrid Falque, Agnès Guiderdoni, Walter S. Melion, Kees Schepers, Paul J. Smith, and Elliott D. Wise"--